2021
DOI: 10.21203/rs.3.rs-138236/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Implementation of Transbronchial Lung Cryobiopsy in a Tertiary Referral Center for Interstitial Lung Diseases – A Cohort Study on Diagnostic Yield, Complications, and Learning Curves

Abstract: BackgroundTransbronchial lung cryobiopsy (TBLC) has been introduced as an alternative to surgical lung biopsy (SLB) in the diagnostics of interstitial lung diseases (ILD). Despite controversy on safety, TBLC is increasingly implemented in ILD centers with an apparent diagnostic yield comparable to SLB. The aim of this study was to assess TBLC implementation experiences from a tertiary Danish ILD center regarding diagnosis, complications, and learning curves for TBLC performance.MethodsTBLC was prospectively pe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…The diagnostic yield of TBLC and classification rate of unclassifiable-ILD in this study were similar to those in previous studies (26,29,34). Histopathologic classification of probable UIP was diagnosed in 18.5% of patients, and there was no UIP pattern.…”
Section: Discussionsupporting
confidence: 90%
“…The diagnostic yield of TBLC and classification rate of unclassifiable-ILD in this study were similar to those in previous studies (26,29,34). Histopathologic classification of probable UIP was diagnosed in 18.5% of patients, and there was no UIP pattern.…”
Section: Discussionsupporting
confidence: 90%
“…This must be viewed through the prism of higher morbidity and a very different set of indications in this population. Of note, no procedure‐related deaths were documented 20 . Cryotherapy seems to be a promising new technique for paediatric airway endoscopy suited for a wide range of indications.…”
Section: Introductionmentioning
confidence: 92%
“…Of note, no procedure-related deaths were documented. 20 Cryotherapy seems to be a promising new technique for paediatric airway endoscopy suited for a wide range of indications. However, due to the novelty, lack of experience and safety concerns, there is hesitation about its applicability in the paediatric airway, 21 which has led the European Respiratory Society to call for studies addressing the role of cryotherapy in children.…”
Section: Introductionmentioning
confidence: 99%
“…Studies directly addressing the PICO question were not identified, but three studies were found that evaluated outcomes in early versus late procedures, which was considered as a surrogate for operator experience. Of these, one study reported cumulated sum (CUSUM) scores for some of the prioritised outcomes [45]. However, as these scores were not comprehensible and raw data regarding the outcomes were not published, the Task Force decided to exclude the study from the analyses.…”
Section: Evidence Summarymentioning
confidence: 99%